2019
DOI: 10.5114/hm.2019.85091
|View full text |Cite
|
Sign up to set email alerts
|

The competitive activity structure of highly skilled basketball players on the basis of factor analysis methods

Abstract: Purpose. to analyse and generalize the competitive activity structure on the basis of the hierarchy of technical and tactical indicators of qualified basketball players in won and lost games by using the factor analysis methods. Methods. the study involved 96 professional basketball players who were national team players of countries that took 1-8 places in the final tournament of the European Basketball Championship 2017. technical and tactical indicators of their competitive activity were analysed for reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
2
15
0
4
Order By: Relevance
“…The present experimental study for the first time provided data on grouping technical and tactical indicators of the competitive activity of skilled female basketball players in the final tournament of the European Basketball Championship 2017, with differentiation into won and lost games. The study confirmed the experts' opinion (Doroshenko, Sushko, Koryahin, Pityn, Tkalich, & Blavt, 2019;Teck, Wang, & Mallett, 2012) on the possibility of studying technical and tactical indicators of the competitive activity of skilled female basketball players using principal component analysis in won and lost games, which makes it possible to develop prerequisites for improving the training and competitive process, supplementing the system of knowledge about the general theory of athlete training.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The present experimental study for the first time provided data on grouping technical and tactical indicators of the competitive activity of skilled female basketball players in the final tournament of the European Basketball Championship 2017, with differentiation into won and lost games. The study confirmed the experts' opinion (Doroshenko, Sushko, Koryahin, Pityn, Tkalich, & Blavt, 2019;Teck, Wang, & Mallett, 2012) on the possibility of studying technical and tactical indicators of the competitive activity of skilled female basketball players using principal component analysis in won and lost games, which makes it possible to develop prerequisites for improving the training and competitive process, supplementing the system of knowledge about the general theory of athlete training.…”
Section: Discussionsupporting
confidence: 70%
“…The main purpose of using principal component analysis in the theory of athletic training is to reduce the number of competitive activity indicators based on their classification and determination of the structure of internal relationships. By identifying and grouping the hidden (latent) factors that explain the relationships between basketball players' technical and tactical indicators in the competitive activity, specialists have the opportunity to analyze data on the identified factors, which, to a large extent, determine factor loadings of the competitive activity indicators (at a level close to 70%) (Doroshenko, Sushko, Koryahin, Pityn, Tkalich, & Blavt, 2019;Teck, Wang, & Mallett, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most difficult is to control competitive activities in team sports. First of all, this is related to the multi-factor structure of competitive activity in these sports (Kostiukevych, 2006;Doroshenko, Sushko, Koryahin, Pityn, Tkalich, & Blavt, 2019;Mitova, 2016).…”
Section: Introductionmentioning
confidence: 99%